DESKTOP graffiti - Verhoeven, Thibaut (Aesthetic Investigations, 2015)
And then Christophe showed me his nicely tailored folders. He still accompanied it with the parlé people nowadays treat young managers during their Powerpoint presentations. When the first folder was opened, though, something changed drastically, in a flash. Suddenly the need for explications dropped away. Without a doubt, these were scribbles straight from the gut, vomited onto the paper when the urge was highest. Without parlé or excuse. Surprising!That is when we really started talking, Christophe and I.